Diagnóstico quali-quantitativo do potencial de cultivo florestal do município de Campo Erê/SC - Schwade, Guilherme Moacir (2017)
The change, expansion or diversification of income generating activities in farms requires planning. For that, it is necessary technical and methodological bases available to professionals that do technical assistance and farmers that need this. Therefore, the objective of this work was to use remote sensing techniques and field forestry studies to detect and characterize areas with forest plantations and potential areas for future projects in the municipality of Campo Erê. The study area was all the territory of the municipality of Campo Erê, Santa Catarina State, southern region of the country. The work was divided in two parts, the first made in the laboratory, through remote sensing techniques, making a transfer of all he territory through the software. For that, the territory was divided in four micro-basins with similarity characteristics, to facilitate the classification. The second part was realized in the field, with visits in farms, to take information in loco. The data treatment was did by the calculation of means and relative frequency. It was found that 40.1% of the total area is occupied by agricultural crops and, these, 2.04% was identified as degraded agriculture area. The pasture class represented 24.21% of the territory, which 45.55% of this class was classified as degraded pasture. Forest plantations accounted 4.9% of the municipal territory, comprising by 56% for pine, 39% for eucalyptus, 4% for yerba mate and 1% for araucaria. Regarding the distance of the urban municipal area, 49.5% of the planted forests is more than 15 km away. It was also verified good physical and soil fertility characteristics for existing forest planting, but one low level of the technical forest managements, that was planted with seedlings with low genetic quality and the lack of basic management of invasive plants and pest control, lack of fertilization, generating situations of low productivity. Approximately 6,500 hectares of land are underutilized or inadequately used, especially in the degraded pasture, that totaling 5,267.8 hectares, which corresponds to 11.03% of the entire territory of the municipality. This area is 177.6% larger than the area with existing forest plantations. With the dimensioning of the planted forests of the municipality, there is a solid database to initiate the planning of actions to develop the forest sector and the municipality. With about 5% of the municipal territory occupied by planted forests, there is a very large expansion offer, however, it is necessary to idealize an entire productive chain, mainly in the final part of it, for consumption and sale of the raw material, being the main problem actually found in the municipality. It is suggested that the areas that are in some degradation stage, can become forest plantation. Forestry production can do the soil protection, water resources and biodiversity, helping to maintain environmental services and farmer’s income.